Latihan Pliometrik dan Sprinting Drill untuk Meningkatkan Daya Ledak dan Kecepatan Atlet Sprint 60 Meter Sekolah Dasar - Mohamad Yoga Fandovi Pratama; Bahtiar Hari Hardovi; Ahmad Bahriyanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to examine the effect of plyometric training and sprinting drills on 60-meter sprint speed among elementary school students at SDN Jenggawah 04. The research employed a quantitative experimental method using a pretest–posttest design. A total of 20 students were selected from a population of 30 students and divided into two groups: an experimental group that received plyometric training combined with sprinting drills, and a control group that followed regular training. Sprint speed was measured using a 60-meter sprint test, while lower limb explosive power was assessed through a vertical jump test. The training program was conducted for four weeks with a frequency of three sessions per week. The results showed that the experimental group experienced a significant improvement in sprint performance, with the average running time decreasing from 11.46 seconds to 9.75 seconds (an improvement of approximately 14.92%), whereas the control group showed only a slight improvement. Conclusion, these findings indicate that plyometric training combined with sprinting drills is effective in improving sprint speed and can be recommended as an alternative training program for enhancing sprint performance in elementary school students. Keywords: plyometric training, sprinting drills, sprint speed, 60-meter sprint, elementary school students